Demand theory and economic calculation in a mixed economy - Manmohan Singh, H. K. (London : Allen & Unwin, 1963)
The book is based on a doctoral dissertation approved by the University of London. The first part deals with the Pure Theory of Demand, makes use of material embodied in a comprehensive history of the theory, in both its micro and macro forms. The second part discusses the usefulness of the micro theory of demand in a mixed economy.
"Based on a doctoral dissertation ... University of London."
Includes bibliographical footnotes and index.
rpm 19/09/2017
Loans
Keywords: Supply and demand